Endoscopic management of walled‐off pancreatic necrosis. (23rd October 2014) - Voermans, Rogier P.; Besselink, Marc G.; Fockens, Paul
Abstract Endoscopic management of infected walled‐off pancreatic necrosis is increasingly being performed. Although the role of the interventional endoscopist in treating necrotizing pancreatitis is growing, a multidisciplinary team including dedicated surgeons and interventional radiologists is a condition sine qua non for optimal patient management. Optimal management starts with a correct diagnosis with accurate description of the extent and nature of the inflammatory changes according to the recently updated criteria. This is important to consequently select the correct patients for the correct intervention at the correct interval after onset. When a decision is made to endoscopically intervene in a patient with (infected) pancreatic necrosis, the actual endoscopic technique does not differ much from the first retrospective series published a decade ago. Although endoscopic intervention for pancreatic necrosis is increasingly performed, evidence for superiority of endoscopic treatment over other techniques is still lacking. Dedicated endoscopic accessories for optimal drainage and necrosectomy are still lacking as well. This review provides an overview of current status, technique and recent innovations of endoscopic treatment of walled‐off pancreatic necrosis.